The correlation analysis between the appearance anxiety and personality traits of the medical staff on nasal and facial pressure ulcers during the novel coronavirus disease 2019 outbreak - Xiaodi Kong; Yong Cao; Xiaonian Luo; Lianxiang He (Wiley, 2021)
Abstract Aim To investigate the psychological status of medical staff with medical device‐related nasal and facial pressure ulcers (MDR PUs) during the outbreak of COVID‐19, analyse the correlation between their psychological status and personality traits, so as to provide a reference for personalized psychological support. Design A total of 207 medical staff who were treating the COVID‐19 epidemic from Hunan and Hubei provinces were enrolled in this analytic questionnaire‐based study. Methods We used these measures: Eysenck Personality Questionnaire Short Scale (EPQ‐RSC), Social Appearance Anxiety Scale (SAAS), Positive and Negative Affect Scale (PANAS) and demographic information forms online. Results Medical staff wearing protective equipment are particularly susceptible to nasal and facial MDR PUs, which is increasing their social appearance anxiety; neuroticism is significantly related to social appearance anxiety and negative emotion. We should pay more attention to their psychological state, cultivate good personality characteristics and reduce negative emotions, and thereby alleviate their MDR PUs‐related appearance anxiety.